Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

Fully Worked Solutions: Number System Exam Drills 1

Download as pdf or txt
Download as pdf or txt
You are on page 1of 5

Fully Worked Solutions

1
5. Given logb a = m ⇒ loga b =
CHAPTER 1 Number System m
1
 logc a = n ⇒ loga c =
n
EXAM DRILLS 1 loga c
 logab c =
loga ab
1 1 2 2
– – loga c
(p2) 3 (q4) 6
p3 q 3
=
1. (a) 1 2 = 1 2 loga a + loga b
– – – –
6 3 6 3
p q p q 1
5 n
  =
= p6 1+
1
m
(1 + 3 ) (2 + 3) 2+3 3+3 1
(b) 3 + = 3+
(2 – 3) (2 + 3 ) 4–3 n
  =
=4 3+5 m+1
m
1– 5 1+ 5
2. + 1 m
1+2 5 1–2 5   = ×
n m+1
(1 – 5)(1 – 2 5) + (1 + 5)(1 + 2 5)
=   = m    [Proven]
(1 + 2 5) (1 – 2 5) n(m + 1)
1 – 3 5 + 10 + 1 + 3 5 + 10
=
1 – 20 1 2
6. log3 x = – log3 y
22 3 3
= –
19 × 3: log3 x = 2 – 3 log3 y
2 3–1 33 (2 3 – 1)(1 + 3) + 3 3 (1 – 3) log3 x + 3 log3 y = 2
3. + =
1– 3 1+ 3 (1 – 3)(1 + 3) log3 x + log3 y3 = 2
2 3+6–1– 3+3 3–9 log3 xy3 = 2
=
1–3
xy3 = 32
4 3–4
= xy3 = 9   [Shown]
–2
=2–2 3 1 16
7. log3 12 3 – log3
3 9 1
1
1 1
) 1 3 + 72 1 2
16
16 33
4.
( 7− 3 = log3 12 3 – log3  
 99 
( 3) − ( 7 + 3)
2 2

12
7−  43 
2
= log3 12 3 – log3  2 
( 7 − 3) (
7 + 3)  
 33 
21

12
=  32

(7 + 3 − 2 21) − (7 + 3 + 2 21) 3
= log3 (12 3 )  4 
 
7−3  23 
1 2
= 21 22 × 3 × 32 × 3 3
−4 21 = log3 4
4 −1 23
= × 2 13
21 4 21 = log3 12 3 × 3 6 2
1
=– 2 13
21 = log3 2 + log3 3 6
3

Fully Worked Solutions 1

Chapter_1.indd 1 6/27/2016 9:55:48 AM


2 13 (b) y
= log3 2 +
3 6
13 2
= + log3 2
6 3 x
0 1
8. log3 2 = p ⇒ 2 = 3p
log3 5 = q ⇒ 5 = 3q –1 (1, –1)

(2 × 5)3x – 1 (23)x + 2 = 2
(c) w – zw = 0
23x – 1 · 53x – 1 · 23(x+2) = 2
3p(3x – 1) · 3q(3x – 1) · 33p(x + 2) = 3p z= w
33xp – p + 3qx – q + 3px + 6p = 3p w
36xp + 3qx + 5p – q = 3p
Compare both sides:
= 1 21 2
11++ii 11++ii
11−−ii 11++ii
6xp + 3qx + 5p – q = p
x (6p + 3q) = q – 4p 1 + 2 i + i2
=
q − 4p 1 − i2
 x =
6 p + 3q 1 + 2i − 1
x + yi =
q − 4p 1 − (−1)
    =
3(2 p + q) 2i
9. (log2 x)(log2 y) = 8    
= =i
2
8
 log2 x = ..................... (1) ∴ x = 0, y = 1
log 2 y
log8 xy = 2
log 2 xy
11. (a) arg 1
 m + 3i 
 −2 − i 
= tan–12−2
1
(4th quadrant)
=2 = –1.11 rad (2 d.p.)
log 2 8
m + 3i
log 2 x + log 2 y (b) = 1 – 2i
= 2   (log2 2 = 1) −2 − i
3 log 2 2
 m + 3i = (1 – 2i )(–2 – i )
log2 x + log2 y = 6 ............................... (2) = –2 – i + 4i – 2
Substitute (1) into (2): = –4 + 3i
8 ∴ m = –4
+ log2 y – 6 = 0 ......................... (3)
log 2 y
12. z = 2 – i, z = 4 + 3i, z– = 2 + i
(3) × log2 y: (log2 y)2 – 6 log2 y + 8 = 0 1 2 1
1 1 4 – 3i
Let log2 y = m z–1 + z = 2 + i + ×
2 4 + 3i 4 – 3i
m2 – 6m + 8 = 0 4 – 3i
(m – 2)(m – 4) = 0 =2+i+
16 + 9
m = 2 or      m = 4 4 3
log2 y = 2   log2 y = 4 =2+i+ – i
25 25
y=4      y = 24 = 16 54 22
8 = + i
When y = 4, log2 x = =4 25 25
log 2 4
4
 x = 2 = 16 6 1+i
13. z =
×
8 1–i 1+i
When y = 16, log2 x =
log 2 16 6 + 6i
=
8 1+1
= =2 = 3 + 3i
log 2 2 4
x = 4 z2  = (3 + 3i )2
∴ x = 16, y = 4 or x = 4, y = 16 = 9 + 9i 2 + 18i
= 18i
10. (a) |w| = 12 + (−1)2 = 2 14. z = –5 + 2i y

−1 r = |z| 2
arg w = tan–1 (4th quadrant) z
1 = (−5) + 22 2
q
p
= – rad = 29 –5
x
4

2 Mathematics for Matriculation Semester 1

Chapter_1.indd 2 6/27/2016 9:55:52 AM


Since z is in the second quadrant, 1
= –tan–1
arg z, θ = p – tan–1
2
5 1 2 p
3

= 2.761 rad =–
6
∴ z = 29 (cos 2.761 + i sin 2.761)

15. Let z = a + bi and z = a – bi



11   pp
11 1
=2cos
z2 2 2cos
  
cos
cos
6
1 2
6
6
1 2
pp 
 −−− − + +
6 
i+isin
i+sin
 pp
i sin
sin
6
pp 
 −−− − 
66 6 

= 1cos sin 2


z + 2z 11  pp pp 
=3–i cos −− iisin
zz 22  66 66
a + bi + 2(a − bi)
=3–i (b) z2 = ( 3 – i )2
(a + bi)(a − bi)
3a − bi = 3 – 2 3 i + i2
=3–i
a 2
+ b2 = 3 – 2 3i – 1
3a bi = 2 – 2 3i
2 2
– 2 =3–i
a + b a + b2 y
3a b
2 2
= 3, 2 =1
     a + b a + b2 2
x
q
⇒ a = a2 + b2 ........(1)
b = a2 + b2 ........(2) –2 3

Equate (1) & (2) ⇒ a = b
Substitute a = b into (1) |z | =
2
22 + (−2 3)2
b = b2 + b2 = 16
b – 2b2 = 0
b(1 – 2b) = 0 =4

b = 0 or b =
1
2
arg z2, θ = –tan–1 12 23 2
1 1 = –tan–1 3
But b > 0 ⇒ b = , a =
2 2 p
=–
1 1 3
∴z= + i
   pppp  pppp  
2 2  
 ∴ z2 = 4cos
cos
 
cos
 331 2
3
isin
sin
 1 2
i sin −−−−  
cos −−−− 3+++i+isin   333 3 
1 1 3−i
16. (a)
z
= ⋅
3+i 3−i

1p p
= 4  cos − i sin 
 3 3 2
3−i
=
3+1 1
17. (a)   21 2
 12++77i i   22++i i  24 + 12 i + 14 i − 7
 12
=
  22−−i i    22++i i  4 +1
3 1
= – i 17 26
4 4 = + i
y 5 5
3 y
4 26
q x
5
1 q
x
4 17
5
2

2 2 2 2
2
1  3  1 2 2

2 2 2 2
=  + −  12 + 7 i 17 26
z 
 4   4 =   +  
2−i  5  5
4   = 6.213

12
=  26 
16
12 + 7 i –1  5 
1 arg = tan 
= 2−i 17 
2  
 5 

12
 1 
1  4  26
arg , θ = –tan–1   = tan–1
z  3 17
 4  = 0.992 rad

Fully Worked Solutions 3

Chapter_1.indd 3 6/27/2016 9:55:58 AM


17 26 1
(b) z = + i 4x2 – 1= 0 ⇒ x = ±
5 5 2
or 4x2 + 3 = 0 (no solution)
17 26
⇒ z = – i 1
5 5 When x = ,
y 2
17 3 3
5 x y= =

_ 26
q
11
 1
4 
 2
2

5 1
When x = – ,
2 2 2
2 2 2 2
17 26
| z | =   +  −  = 6.213 3 3
 5  5 y= =–

arg z , θ = –tan–1
26
= –0.992 rad
1 1
 1
4− 
 2
2

17
1 3 1 3
Polar form of z , ∴z= + i or z = – – i
z = 6.213 [cos (–0.992) + i sin (–0.992)] 2 2 2 2
 = 6.213 (cos 0.992 – i sin 0.992) 9. Let z = a + bi, z = a – bi
1
2 2 (a + bi ) + 3(a – bi ) = 20 – 2i
18. (a) z z = ( 5 3 – 5i ) (–1 –
1 2 3 i )
4a – 2bi = 20 – 2i
= (50 – 50 3 i )(–1 – 3 i ) 4a = 20 ⇒ a = 5
2b = 2 ⇒ b = 1
= –50(1 – 3 i )(1 + 3 i )
∴z=5+i
= –50(4)
z – 6 = (5 + i ) – 6
z12z2 = –200 [Shown, where k = –200] = –1 + i
(b) z2z2 = 2 y
(x + yi )2(–1 – 3 i ) = 2 1
z–6
2
x2 – y2 + 2xyi = q
−1 − 3i x
–1

=
2
 2
 −1 + 3i 

−1 − 3i  −1 + 3i  2 arg (z – 6) = p – tan–1 1
=p–
p
−2 + 2 3i 4
= 3p
1+ 3 =     [Shown]
4
−2 + 2 3i
=
4 4 2+i
1 3 20. z = ⋅
=− + i 2−i 2+i
2 2 8 + 4i
Compare both sides: =
5
1 8 − 4i
x2 – y2 = − .......................(1) z=
2 5
3 1 8 − 4i 1
2xy = z + = +
2 z 5 8 + 4i
3 5
  y = .......................(2)
4x 8 − 4i 5
= +
5 8 + 4i
3
Substitute y = into (1): (8 − 4 i)(8 + 4 i) + 5(5)
4x =
22 5(8 + 4 i)
 3
2
x – 1 2 
 4x 
=–
1
2 =
64 + 16 + 25
5(8 + 4 i)
3 1
x2 – =– 21 8 − 4 i
16 x 2 2 = ⋅
8 + 4i 8 − 4i
× 16x : 16x4 – 3 = –8x2
2
4x2 –1 –4x2
16x4 + 8x2 – 3 = 0 4x2 3 +12x2 218( − 4 i)
=
(4x2 – 1)(4x2 + 3) = 0 16x –3 +8x2
4
80

4 Mathematics for Matriculation Semester 1

Chapter_1.indd 4 6/27/2016 9:56:04 AM


21 21 −1 − 12 i
= – i =
10 20 145
1 12
21. (a) (z + i )(z – 3) = (2 + 3i + i )( 2 + 3i – 3) =– – i
145 145
= (2 + 4i ) (–1 + 3i )
y
= –2 + 2i –12
1
= –14 + 2i 145 x
y q
12
2
145
q
x

1 1 1 1
2 2
–14 1  1   12 
= − + −
z2 + 4  145  145
|(z + i )(z – 3)| = (−14)2 + 22
1
= 200 =
145
= 10 2
145
=
2 145
argument, θ = p – tan–1

1 2
14  12 
= 2.9997 rad  −1 145 
argument, θ = –  p − tan
1 
∴ (z + i )(z – 3) = 10 2 (cos 2.9997 + i sin 2.9997)  
 145 
1 1 = –(p – tan–1 12)
(b) =
z + 4 (2 + 3i)2 + 4
2
= –1.654

=1
−−11++12 21
 11 −−11−−12

12ii

12ii
12ii −−11−−12 2 ∴
1
=
145
z 2 + 4 145
[cos (–1.654) + i sin (–1.654)]

Fully Worked Solutions 5

Chapter_1.indd 5 6/27/2016 9:56:06 AM

You might also like